2021
DOI: 10.1016/j.csbj.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral sequence reconstruction - An underused approach to understand the evolution of gene function in plants?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 231 publications
0
7
0
Order By: Relevance
“…There are challenges to examining these timelines experimentally. 102,103 However, with increased taxa sampling and increasingly sophisticated phylogenomic methods, we are beginning to piece together how BGCs emerged and diversied.…”
Section: Cluster Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are challenges to examining these timelines experimentally. 102,103 However, with increased taxa sampling and increasingly sophisticated phylogenomic methods, we are beginning to piece together how BGCs emerged and diversied.…”
Section: Cluster Evolutionmentioning
confidence: 99%
“…Attempts to understand the birth of a BGC may involve identifying the ancestral gene composition of relevant loci using comparative genomics, and predicting the activities of ancestral genes using phylogenetics, annotation or experimentation. The BGC responsible for nepetalactone biosynthesis in Nepeta was investigated using such an approach, including ancestral sequence reconstruction 100,103 (Fig. 7).…”
Section: Tracking Cluster Originsmentioning
confidence: 99%
“…A previous study that included a panel of 145 wild-type microbial esterases unambiguously concluded that there is a direct relationship between enzyme enantioselectivity and substrate specificity . In addition, ancestral enzymes are generally considered to have a broader substrate scope compared to enzymes sourced from extant genes . The enantioselectivity results of our 101-enzyme panel when tested with substrate 1a support this general scientific consensus.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Functional studies in emerging genetic models of extant streptophyte algae should help answer these questions (Zhou et al , 2020). Likewise, reconstructing ancestral proteins could help to understand the evolutionary trajectory that caused the auxin responses, protein structure, and function to diverge in the green lineages (Scossa & Fernie, 2021).…”
Section: Giant Steps…mentioning
confidence: 99%